Cross-sectional association between plasma aldosterone concentration and cognitive performance by mini-mental state examination in community dwellers - Nusufujiang, Aketilieke; Heizhati, Mulalibieke; Li, Nanfang; Yao, Ling; Yang, Wenbo; Wang, Hui; Li, Mei; Gan, Lin; Maitituersun, Adalaiti; Liu, Miaomiao; Nuermaimaiti, Qiaolifanayi; Cai, Li; et al. (Frontiers in Nutrition, 2025)
BackgroundAldosterone is the effector hormone in the renin angiotensin aldosterone system and existing data suggest aldosterone affect cognitive function. However, the relationship between plasma aldosterone concentration (PAC) and cognitive performance remains unexplored in community dwellers. Therefore, we aimed to explore whether PAC is associated with cognitive performance in this population.MethodsWe cross-sectionally enrolled adults using multistage random sampling from Emin, China in 2019. Participants underwent questionnaires and data collection. Cognitive status was assessed using mini-mental state examination (MMSE) questionnaire. Multi-variable linear and logistic regression were used to explore the association between log PAC and log MMSE score, and between tertiled PAC (the higher PAC as the exposure) and low cognitive performance, respectively, in total, apparently healthy and diseased participants. Subgroup analyses also were performed by age, gender, BMI, living region, ethnicity and education attainment status.Results27,707 subjects were included, of whom, 12,862 were apparently healthy and 14,845 had disease. Log-PAC was positively associated with log-MMSE score in the multivariable linear regression in the total (B = 0.01, 95%CI: 0–0.01, p < 0.001), apparently healthy (B = 0.01, 95%CI: 0–0.01, p = 0.007) participants, and the diseased without taking medicine (B = 0.01, 95%CI: 0.01–0.02, p = 0.004) participants. In logistic regression, the highest third tertile of PAC group showed significantly lower odds for the presence of low cognitive performance in total (OR = 0.83, 95%CI: 0.73–0.93, p = 0.002) and diseased without taking medicine participants (OR = 0.70, 95%CI: 0.57–0.86, p < 0.001). Various sub-group analysis showed largely consistent results with the main analysis.ConclusionThere was a positive correlation between plasma aldosterone and cognitive functions in community dwellers, whereas further studies are need when considering the cross-sectional nature of the current study.